A bibliometric and visual analysis of the use of ustekinumab in Crohn’s disease using CiteSpace - Chen, Yi; Zhang, Jiaqi; Wu, Junling; Zhang, Hanwen; Luan, Zhe; Zhao, Zhizhuang; Li, Congyong; Zhao, Yiming; Zhang, Hu; Wang, Shufang; Sun, Gang (Frontiers in Pharmacology, 2024)
Background: The novel biologic agent ustekinumab (UST), a monoclonal antibody against the p40 subunit of interleukin-12 and interleukin-23, has been applied in the treatment of Crohn's disease (CD). With the development of relevant research, the clinical treatment and favorable prognosis of UST in CD have garnered considerable attention. However, there is a lack of reports that present the current status of UST-related studies in a comprehensive and objective manner. Consequently, this study aims to visually analyze the current status and clinical trends of UST-related research, identify leading researchers, and recognize deficiencies using bibliometrics and knowledge mapping, which might assist in understanding future research priorities in that specific field. Methods: Published articles containing the use of UST in CD were retrieved from the Web of Science core collection database between 2008 and 2022. Then, the bibliometric analysis was performed, and a knowledge map was generated and visualized using the CiteSpace software. Results: A total of 479 articles published between 2008 and 2022 were included in the bibliometric analysis. These publications were authored by 185 scholars from 51 countries or regions, among which the United States (38.3%), Canada (16.9%), and England (10.0%) were predominant in publishing. The keyword analysis indicated that UST has long been a popular biologic agent, and its clinical efficacy, safety, and indication for vulnerable populations in CD are popular research topics. The phrase "fecal calprotectin", a biomarker reflecting the degree of disease activity and monitoring the therapeutic response, began to gain traction in 2020 and has continued to this day. Looking for UST-related biomarkers was gaining clinical attention. The number of clinical studies involving the outcome of UST treatment in CD patients has increased, with the current research focusing on efficacy, safety, indications for vulnerable populations, therapeutic drug monitoring, and biomarkers. As an alternative drug after the failure of traditional immunosuppressive therapies or TNF-α antagonist therapy, UST is an effective and safe therapy in real-world refractory CD patients. UST will remain an active candidate for research in the treatment of CD.